Biological Function of Short-Chain Fatty Acids and Its Regulation on Intestinal Health of Poultry - Liu, Lixuan; Li, Qingqing; Yang, Yajin; Guo, Aiwei (Frontiers in Veterinary Science, 2021)
Short-chain fatty acids (SCFAs) are metabolites generated by bacterial fermentation of dietary fibre (DF) in the hindgut. SCFAs are mainly composed of acetate, propionate and butyrate. Acetate is produced from pyruvate via acetyl-CoA and the Wood-Ljungdahl pathway. Phosphoenolpyruvate synthesises propionate through the succinic acid or acrylate pathways, whereas butyrate is synthesised by two molecules of acetyl-CoA. Many studies have shown that SCFAs play a significant role in the regulation of intestinal health in poultry. SCFAs are primarily absorbed from the intestine and used by enterocytes as a key substrate for energy production. SCFAs can also inhibit the invasion and colonisation of pathogens by lowering the intestinal pH. Additionally, butyrate inhibits the expression of nitric oxide synthase (NOS2), which encodes inducible nitric oxide synthase (iNOS) in intestinal cells via the PPAR-γ pathway. This pathway causes significant reduction of iNOS and nitrate, and inhibits the proliferation of Enterobacteriaceae to maintain overall intestinal homeostasis. SCFAs can enhance the immune response by stimulating cytokine production (e.g. TNF-α, IL-2, IL-6, and IL-10) in the immune cells of the host. Similarly, it has been established that SCFAs promote the differentiation of T cells into T regulatory cells (Tregs) and expansion by binding to receptors, such as Toll-like receptors (TLR) and G protein-coupled receptors (GPRs), on immune cells. SCFAs have been shown to repair intestinal mucosa and alleviate intestinal inflammation by activating GPRs, inhibiting histone deacetylases (HDACs), and downregulating the expression of pro-inflammatory factor genes. Butyrate improves tight-junction-dependent intestinal barrier function by promoting tight junction (TJ) assembly. In recent years, the demand for banning antibiotics has increased in poultry production. Therefore, it is extremely important to maintain the intestinal health and sustainable production of poultry. Taking nutrition strategies is important to regulate SCFA production by supplementing dietary fibre and prebiotics, SCFA-producing bacteria (SPB), and additives in poultry diet. This review summarises the biological functions of SCFAs and their role in gut health, as well as nutritional strategies to regulate SCFA production in the poultry gut.